Community Perceptions on Ecotourism Development in Sebangau National Park, Central Kalimantan, Indonesia - Yulianti, Lisna; Pratiwi, Yun; Cheyne, Susan M; Kadhafi, Andi Muhammad (Journal of Indonesian Tourism and Policy Studies, 2024)
Sebangau National Park (SNP), Central Kalimantan, Indonesia, is home to the world’s largest contiguous population of orangutans (Pongo pygmaeus wurmbii) and a vast number of other fauna and flora. Ecotourism is a developing activity in this region and has the support of regional and national governments and possibilities for local, national and international tourism are extensive. In this case study we investigate perceptions of the local community in the village of Kereng Bangkirai to ecotourism through the following topics: 1) Ecotourism Development, 2) public tourist presence and visits, 3) how involved local people are in SNP management, 4) effects of ecotourism on local economic enterprise, 5) impact on community capacity building and 6) overall impacts of ecotourism to the local community. We interviewed 250 people using semi-structured interviews and questionnaires. Analysis was carried out using descriptive statistics, carried out in SPSS 30.0.0 (https://www.ibm.com/products/spss-statistics). We show that overall, there are positive benefits from the presence of the national park and tourists but not all interventions or actions by SNP are universally accepted. We showcase the importance of including local people in protected area management especially ecotourism. This format of involving local communities can be a model for other sites in Indonesia interested in implementing ecotourism activities.